Religion and Socio-Political Dynamics in Nepali History: Analyzing Consciousness, Class, and State Power - Karki, Chakra Bahadur; Chetri, Neel Kumar (Medha: A Multidisciplinary Journal, 2025)
This paper examines the philosophy of Pasupata Shaivism and its socio-political impact on Nepali history, focusing on the relationship between ideology, class hierarchy, and state power. Central to this philosophy is the transactional relationship between consciousness and matter, where human interaction with the world through the five senses shapes the mind, influenced by karma (human actions). This dynamic interplay suggests that matter and consciousness are interdependent, reflecting a deeper principle of contradiction—where the existence of an entity relies on the coexistence of opposing conditions. The study argues that Pasupata Shaivism’s egalitarian principles, emphasizing collective well-being, spiritual equality, and shared resources, historically strengthened the Nepali state and fostered social cohesion. In contrast, periods dominated by Dharmasastra traditions, which advocated for private property and caste hierarchies, exacerbated class divisions and state fragility. Using primary sources such as inscriptions, genealogies, and religious texts, along with secondary analyses, the paper explores the socio-political implications of Pasupata Shaivism’s focus on material conditions (dravyani), skills and knowledge (guna), and human actions (karma). Findings highlight how Shaivism supported peasants and workers, promoting social harmony and challenging exploitative systems, while Smriti-based frameworks concentrated wealth and power among elites. The paper concludes that Pasupata Shaivism offers an indigenous framework for addressing social inequalities and fostering equitable governance.